Pinocembrin flavanone inhibits cell viability in PC-3 human prostate cancer by inducing cellular apoptosis, ROS production and cell cycle arrest - Shao Linhai; Shao Yajun; Yuan Yu (Acta Pharmaceutica, 2021)
The main purpose of the present study was to evaluate the antitumor effects of pinocembrin in human prostate cancer cells (PC-3) along with investigating its effects on cell apoptosis, endogenous ROS production and cell cycle. MTT assay and clonogenic assays were used to study the effects on cell viability and cancer colony formation, respectively. Fluorescence microscopy along with Western blotting was used to study apoptotic effects induced by pinocembrin. Flow cytometry was used to study effects on ROS production and cell cycle phase distribution. Results indicated that pinocembrin promoted inhibition cell proliferation along with reducing cancer colony formation of PC-3 cells in a dose-dependent manner. Pinocembrin induced regulatory effects over expressions of caspase-3, caspase-9, Bax and Bcl-2, thereby promoting apoptotic cell death in PC-3 cells. It also led to the dose-dependent G0/G1 cell cycle arrest. In conclusion, pinocembrin exhibits strong anticancer effects in human prostate cancer cells mediated via apoptosis, endogenous ROS production and G0/G1 cell cycle arrest.